Perceived professional identity formation and influencing characteristics among speech pathology students - Abigail Lewis; Denise Jackson; Dawn Bennett (Journal of Teaching and Learning for Graduate Employability)
While professional identity formation (PIF) is an important facet of employability and becoming a health professional, there has been little research on PIF among speech pathology (SP) students. This single group, cross-sectional study explored perceived PIF among SP students at a large, urban, Australian university selected via stratified sampling from a four-year undergraduate program. Using an established online self-assessment tool to measure perceived employability, the study reports on seven related constructs relevant to PIF. The self-assessment has previously been found to have strong validity and reliability and the subset used in this study likewise had strong validity and reliability. There were 84 participants and the PIF constructs were: self and program awareness (SPA); identification with commitment (IC); reconsideration of commitment (RC); self-esteem (SE); perceived program relevance (PPR); career exploration and awareness (CEA); and ethical and responsible behaviour (ERB). Descriptive and multivariate statistics were used to estimate the proportion of variance for year level and individual characteristics for each construct and overall PIF. Perceived professional identity increased from first to fourth year, significant only for SPA, IC and PPR constructs. Students aged over 25 years self-rated significantly higher on ERB than younger students, as did students studying part-time compared to those studying full-time. Participants not engaged in paid work had significantly higher SE than those who were working, as did students from low socio-economic status (SES) compared with medium or high SES students. No differences were found for other individual characteristics, although some group sizes were very small. Recommendations to enhance PIF include incorporating a range of reflective activities, assertiveness training and opportunities to explore ethical dilemmas within the curriculum.